Taking Prison to Court: Exploring the Judicial Review of Prison Decision-Making Through Supreme Court Judges in Israel - Dagan, Netanel (The British journal of criminology, 2024)
Scholars have criticized the gap between judicial work and the realities of prison life. In this article, drawn from qualitative findings from Supreme Court Judges in Israel, we analysed how such Judges negotiate their administrative judicial review over prison officials’ decisions. We found that through their judicial review, the Judges either bureaucratise, re-sentence the prisoner or reform prison life. Each theme imagines differently both the purpose of judicial review, as well as the values, emotions, legal ‘tool-kit’, and players (prison service, the claiming prisoners) involved in the review process. The findings move the scholarly focus of judicial decision-making from the quantity to the quality of punishment and expand the understanding of judicial consciousness regarding prison life.